2017
DOI: 10.1007/s12272-017-1000-4
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from Narcissus poeticus cv. Pink Parasol of various structural types and their biological activity

Abstract: Fifteen Amaryllidaceae alkaloids (1-15) of various structural types were isolated by standard chromatographic methods from fresh bulbs of Narcissus poeticus cv. Pink Parasol. The chemical structures were elucidated by MS, and 1D and 2D NMR spectroscopic analyses, and by comparison with literature data. Narcipavline (5) and narcikachnine (6) are reported here for the first time. In their structure are combined two basic structural types of Amaryllidaceae alkaloids (galanthamine- and galanthindole-structural typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…All Amaryllidaceae alkaloids tested have been previously isolated at the Department of Pharmaceutical Botany, Faculty of Pharmacy in Hradec Králové from various Amaryllidaceae plant species ( Zephyranthes robusta [ 39 , 40 ], Chlidanthus fragrans [ 27 , 41 ], Nerine bowdenii [ 42 ], Narcissus poeticus cv. Pink Parasol [ 43 ], and N. poeticus cv. Brackenhurst [ 44 ]).…”
Section: Methodsmentioning
confidence: 99%
“…All Amaryllidaceae alkaloids tested have been previously isolated at the Department of Pharmaceutical Botany, Faculty of Pharmacy in Hradec Králové from various Amaryllidaceae plant species ( Zephyranthes robusta [ 39 , 40 ], Chlidanthus fragrans [ 27 , 41 ], Nerine bowdenii [ 42 ], Narcissus poeticus cv. Pink Parasol [ 43 ], and N. poeticus cv. Brackenhurst [ 44 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Ancistrocladus tectorius [84] Ancistrocladus ealaensis [86] Ancistrocladus ealaensis [32] T A B L E 1 (Continued) Amaryllidaceae family [98] Narcissus poeticus cv. Pink Parasol [99] (Continues) The alkaloids in this classification have the simplest structures and are distributed mainly in the genera Papaver,…”
Section: 4′-oo-didemethylancistrocladinium a (A/b)mentioning
confidence: 99%
“…24,103 The pyrrolophenanthridine alkaloids seco-isopowellaminone (336), haemanthamine (326), and incartine (337) also exhibited weak anti-human AChE activity. 99 (+)-Parfumidine (79), a spirobenzylisoquinoline alkaloid, exhibited POP inhibitory activity with an IC 50 value of 99 µM, compared with 3.27 µM for the positive drug (Z)-pro-prolinal. 24 The known benzophenanthridine alkaloid chelerythrine potently and selectively inhibited an isoform of recombinant human monoamine oxidase A (MAO-A) with an IC 50 value of 0.55 μM.…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
“…The AA are classified into 9 main structural types (crinine, galanthamine, haemanthamine, homolycorine, lycorine, montanine, narciclasine, norbelladine, and tazettine) alongside more than 10 others (plicamine, galanthindole, augustamine, graciline, etc.). These minor structure types are usually found in trace amounts and are most often represented by single alkaloids [9,10]. Galanthamine, a selective, competitive acetylcholinesterase inhibitor with antioxidant properties is the most important AA identified so far.…”
Section: Introductionmentioning
confidence: 99%
“…For commercial production of AAs, the cultivars are preferred over native species because of their availability. Some Narcissus cultivars have been already studied in detail, and a number of AAs have been isolated throughout the years [7,10,21]. From previous phytochemical studies of 40 differing Narcissus cultivars, 14 AAs were identified in the alkaloid extract of Narcissus cv.…”
Section: Introductionmentioning
confidence: 99%